(3dWGFa GdeYGQas - (3eMeO Hf YHO Gddg Hf WGgQ GdfjSGHhQjs ((3jhSa Hf YHO Gddg GdOjQjfi s)
(3ChdgG (B:s
(3gPG eG GNJQJg ef GdJhGQjN hGdSjQ hcJH GdeYGQa , hSejJg HdWGFa GdeYGQa deG ajg ef GdCNHGQ GdZQjHI hGdGJaGbGJ GdYLjHI s
(3Hg VHWs
(3eUhQ HGdahJhSJGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B515 s
Keywords: (3GdCOHs